Comparison of fish biomass and fish carbon content associated with reef sites at the Rio Grande Valley artificial reef in the Gulf of Mexico - Allison K. White; Md Saydur Rahman; Richard J. Kline (PLoS ONE, 2026)
As global fisheries stocks have decreased due to overfishing and climate change, artificial reefs have gained significant attention. In addition to providing or restoring habitat, artificial reefs may serve as carbon capture sinks and potential climate mitigation strategies. The Rio Grande Valley (RGV) Reef is an artificial reef located in the northwestern Gulf of Mexico off the coast of Texas. The RGV Reef area spans 1,650 acres and is comprised of hundreds of groupings of recycled and pre-formed materials ranging from low relief (1–2 ft) to high relief (8–30 ft) reef structures. This reef provides a variety of novel habitat stepping-stones for multiple fish species at different life stages and supports local fisheries. Since the deployment of reef structures, fish biomass and abundance are substantially higher than expected for unconsolidated soft-bottom habitats; however, quantifying fish biomass is necessary to evaluate the relative effectiveness of different structural types. For this study, a Simrad EK80 split-beam sonar was used to estimate fish biomass at the reef sites. Biomass was calculated using fish echo returns and length-weight relationships. The standing stock of fish carbon contained within the fish populations associated with the RGV Reef was assessed using literature-derived measurements. The total fish biomass within the RGV Reef area was estimated at 24.4 tons, equating to 2.81 metric tons of carbon within the fish population. This study provides important information on the factors influencing fish biomass in this reef and the amount of carbon held in fish biomass within a previously overlooked potential blue carbon ecosystem.